The Driving Factors of Public’s Interest in The Use of QRIS to Achieve Cashless Society - Risky Angga Pramuja; Arif Prasetyo Wibowo; Dedik Fitra Suhermanto (Optimum: Jurnal Ekonomi dan Pembangunan, 2021)
The market serves as a traditional market that has been renovated by the local government to transform the traditional system into a modern market without abandoning its traditional traits. On the other hand, the modern system refers to improved sanitation and payment mechanisms. The payments in traditional markets have been done by using cash, but the modern market system promotes non-cash payments. In this case, the non-cash payments are implemented using a barcode scanning system provided by the Indonesian national bank under the name QRIS. Therefore, an in-depth study was essential to be carried out to understand the public’s interest in the use of QRIS or non-cash for transactions in the Oro-Oro Dowo Market. The research methods used in this study were field research and survey. For the data analysis, several theories were applied, namely Theory of Reasoned Action (TRA), Theory of Planned Behaviour, and Technology Acceptance Model (TAM). Then, the theories were analyzed by utilizing a software called SMART PLS to identify whether there was a correlation and effect of the use of QRIS and the buying interest or transaction rates in the Oro-Oro Dowo Market. The results of this study indicate that the three variables of reliability, construct validity, structural model, and discussions related to complexity, the usefulness of QRIS, time constraints, ease of use, and e-learning self-efficiency show appropriate consistency as most of the respondents used QRIS as an electronic transaction system that allowed them to do a faster transaction due to its efficiency and accessibility